Application of Dipping on CaCl2 as a Postharvest Treatment to Maintain the Quality of Pineapple during Storage - Tamalea, Rafi Reynaldi; Haryanti, Pepita; Wibowo, Condro (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2021)
Pineapple is a perishable agricultural products, therefore it needs an appropriate treatments at the postharvest stage. An appropriate treatment will contribute on maintaining the quality and prolong shelf life of the products. Recently, several efforts have been conducted to achieve the purposes. Moreover, appropriate treatments are still required for alternatives solution of pineapples producers. This study aims to determine the effect of the dipping on CaCl2 solution at various concentration on physical (mold incidence and mold severity), chemical (pH value) and sensory properties (color, texture, aroma, taste, and overall acceptance) of pineapple during storage. The dipping of the fruits were conducted at hot condition (50℃). The samples were MD-2 pineapple with two different classification of shell color (shell color 0 and shell color 2). The results showed that there was no significant effect of CaCl2 application treatment by dipping in hot water (50℃) on the parameters of pH value. The incidence and severity of mold were detected after 16th of storage on treated samples and the control. After storage for 40th days, the treated sample had better sensory properties, particularly on texture, color, and overall acceptance.